A longitudinal examination of the relationship between teacher burnout and depression. Issue 3 (2nd September 2013) - Shin, Hyojung; Noh, Hyunkyung; Jang, Yoojin; Park, Yang Min; Lee, Sang Min
Abstract : This study investigates the longitudinal relationships between burnout and depression among teachers. Middle and high school teachers participated in a 3‐wave survey. The results of the latent growth modeling analysis revealed that there was a significant relationship between the initial status of burnout and the initial status of depression. Results also indicated a significant relationship between the change rate of burnout and the change rate of depression. Moreover, the autoregressive cross‐lagged modeling revealed a causal relationship such that teacher's burnout leads to subsequent depression symptoms, not vice versa.